2019
DOI: 10.1044/2019_aja-19-0011
|View full text |Cite
|
Sign up to set email alerts
|

Sensory and Cognitive Components of Auditory Processing in Individuals With Tinnitus

Abstract: Purpose The main purpose of the study is to explore the auditory selective attention abilities (using event-related potentials) and the neuronal oscillatory activity in the default mode network sites (using electroencephalogram [EEG]) in individuals with tinnitus. Method Auditory selective attention was measured using P300, and the resting state EEG was assessed using the default mode function analysis. Ten individuals with continuous and bothersome tin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…However, few studies take a different view. In addition, increased N1 response has been found in a few studies [ 94 , 95 , 96 ], which corresponds to abnormal center gain. Moreover, increased neural synchronization or neuronal maladaptation are possible causes.…”
Section: Electrophysiological Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, few studies take a different view. In addition, increased N1 response has been found in a few studies [ 94 , 95 , 96 ], which corresponds to abnormal center gain. Moreover, increased neural synchronization or neuronal maladaptation are possible causes.…”
Section: Electrophysiological Methodsmentioning
confidence: 99%
“…Increased latency of P3 without amplitude change was found in tinnitus patients in the majority of studies [ 73 , 93 , 99 ], while other studies found that the amplitude of P3 in tinnitus patients was significantly lower than in controls and there is no difference in latency [ 89 , 91 , 92 , 100 , 101 ]. Furthermore, larger P3 amplitudes along with prolonged latency were observed in individuals with tinnitus [ 96 ]. The impaired adaptive capacity of cortical neurons, wider firing range of neurons, and changes in the baseline activation of neurons leading to hyperexcitability of neurons can all lead to P3 enlargement [ 96 ].…”
Section: Electrophysiological Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…P3 is reported to be altered in individuals with tinnitus, which indicates attentional dysfunction. 20 21 22 23 24 25…”
Section: Introductionmentioning
confidence: 99%
“…There have been shreds of evidence that tinnitus affects either or both the sensory and cognitive components of CAEPs, suggesting a difference in the way sound is being processed. 20 21 22 23 24 25 26 27 28 In vitro animal studies 16 have shown that the hyperactive neural firings decrease as a result of RIT. However, there are no neurophysiological studies reported on humans following RIT or educational counselling.…”
Section: Introductionmentioning
confidence: 99%